Hydrothermal preparation method of CuAgSe micromaterial and near room temperature thermoelectric application thereof
Patent Information
- Application Number
- CN202611236465.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明的目的在于提供一种CuAgSe微米材料的水热制备方法及其近室温热电应用,以解决现有CuAgSe胶体纳米晶或纳米粉体易团聚、部分制备方法存在有机配体残留、后续热压成型条件敏感以及块体结构稳定性不足等问题
[0028] (1) Controllable preparation of CuAgSe micron particles: This invention introduces 1.5-2.0 mol/L of alkali metal hydroxide into an aqueous selenium-containing precursor system and combines it with a hydrothermal reaction at 160-200 °C. The nucleation and growth of CuAgSe are regulated by the synergistic effect of the strongly alkaline environment and the hydrothermal crystallization process, resulting in CuAgSe micron powder with a main particle size of 2-3 μm and relatively pure phase. This method uses water as the reaction medium and does not use organic ligands such as oleylamine or dodecyl mercaptan, or high-boiling-point organic solvents, which can reduce the problems of organic residues and severe agglomeration of nanoparticles. At the same time, a highly active selenium-containing precursor system is constructed by reducing selenium powder with sodium borohydride, and the controllable growth of CuAgSe from the nanoscale to the microscale is achieved by combining it with a hydrothermal reaction, providing a new technical path for obtaining high-quality CuAgSe micron thermoelectric powder.
Smart Images

Figure CN122916062A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy materials technology, specifically to a hydrothermal preparation method of CuAgSe micron-sized material and its near-room temperature thermoelectric application. Background Technology
[0002] Thermoelectric materials can directly convert heat energy into electrical energy, and have promising applications in waste heat recovery, thermal management of electronic devices, and refrigeration. Near-room temperature heat sources are widely distributed, but typically have small temperature differences and low energy quality; therefore, developing high-performance materials suitable for near-room temperature thermoelectric conversion is of great significance. The performance of thermoelectric materials is usually characterized by the dimensionless thermoelectric figure of merit zT, expressed as zT = σS 2 T / κ, where σ is the electrical conductivity, S is the Seebeck coefficient, κ is the thermal conductivity, and T is the absolute temperature. Since these transport parameters are interrelated, achieving synergistic regulation of electrical and thermal transport properties is key to improving near-room temperature thermoelectric performance.
[0003] CuAgSe is a ternary selenide superionic conductor with "phonon liquid-electron crystal" transport characteristics, exhibiting high carrier mobility and low lattice thermal conductivity (κ). L CuAgSe is a promising near-room-temperature N-type thermoelectric material. It mainly exists in a low-temperature ordered phase and a high-temperature superionic phase. At room temperature, it is predominantly orthorhombic, while the high-temperature phase is cubic. A structural phase transition and change in conductivity occur around 470-500 K. Although the low-temperature phase has a high σ, its absolute value of S is relatively small, and its electronic thermal conductivity (κ) is low. e The relatively high temperature and humidity limit further improvement in overall thermoelectric performance.
[0004] Existing CuAgSe materials can be prepared using methods such as melting, mechanical alloying, high-temperature solid-state reaction, and liquid-phase synthesis. High-temperature preparation methods typically suffer from high energy consumption, loss of volatile components, and difficulty in controlling powder morphology. Some liquid-phase methods rely on organic solvents or ligands such as oleylamine and dodecyl mercaptan, which have drawbacks including complex processes, numerous post-processing steps, and difficulty in fully removing organic ligands. Furthermore, the resulting nanocrystals have small particle sizes and large specific surface areas, making them prone to agglomeration and highly sensitive to ligand removal, heating / cooling processes, and hot-pressing parameters. In addition, CuAgSe undergoes crystal structure and volume changes near the phase transition, which may lead to thermal stress accumulation, increasing the risk of bulk deformation, cracking, or hot-pressing mold failure. Therefore, there is a need to develop a preparation method that does not use organic solvents and ligands, has well-defined reaction parameters, and can obtain CuAgSe micron-sized powders to improve the powder's adaptability to sintering and provide a material basis for the preparation of near-room-temperature thermoelectric bulk materials. Summary of the Invention
[0005] The purpose of this invention is to provide a hydrothermal preparation method for CuAgSe micron-sized materials and their near-room-temperature thermoelectric applications, addressing the problems of easy agglomeration of existing CuAgSe colloidal nanocrystals or nanopowders, residual organic ligands in some preparation methods, sensitivity to subsequent hot-pressing conditions, and insufficient bulk structural stability. This invention introduces a specific concentration of sodium hydroxide into an aqueous precursor system containing reduced selenium species (NaHSe), and combines this with a hydrothermal reaction to regulate the nucleation and grain growth of CuAgSe, obtaining CuAgSe powder with relatively pure phase and micron-sized particle morphology. The obtained powder can be further annealed and hot-pressed to form a dense bulk for near-room-temperature thermoelectric conversion.
[0006] In one aspect of the present invention, a hydrothermal preparation method for CuAgSe micromaterials is provided. According to an embodiment of the present invention, the method includes the following steps:
[0007] (1) Under an inert atmosphere, the selenium source was added to an aqueous solution containing sodium borohydride and stirred to react, resulting in a precursor solution containing reduced selenium species.
[0008] (2) Add alkali metal hydroxide to the precursor solution to make the concentration of alkali metal hydroxide 1.5-2.0 mol / L based on the initial aqueous phase volume; then add copper nitrate trihydrate and silver nitrate in a molar ratio of Cu, Ag and Se of 1:1:1 and stir to obtain a mixed reaction solution;
[0009] (3) Place the mixed reaction solution in a sealed reaction container and carry out a hydrothermal reaction at 160-200 °C for 12-24 h;
[0010] (4) After the reaction is completed, the product is cooled, and the product is subjected to solid-liquid separation, washing and drying to obtain near-room temperature CuAgSe micron thermoelectric material.
[0011] The alkali metal hydroxide is used to provide a suitable strongly alkaline reaction environment, regulate the stability of the reduced selenium precursor species, and promote the nucleation and grain growth of CuAgSe. Its concentration is controlled at 1.5-2.0 mol / L, which is beneficial for the full reaction of the copper and silver sources with the selenium-containing precursor and promotes the stable formation of CuAgSe micron-sized particles.
[0012] In addition, the hydrothermal preparation method of CuAgSe micromaterial according to the above embodiments of the present invention may also have the following additional technical features:
[0013] In some embodiments of the present invention, in step (1), the molar ratio of the selenium source to sodium borohydride is 1:(2-3), the stirring reaction time is 0.5-1 h, and the inert atmosphere is nitrogen or argon. An appropriate excess of sodium borohydride helps compensate for its loss in the aqueous solution and promotes the full conversion of selenium powder into reduced selenium precursor species. The inert atmosphere is used to isolate oxygen from the air, reduce the oxidation consumption of sodium borohydride and the oxidation of reduced selenium precursor species, and help maintain a stable reduction reaction environment. The selenium source is preferably selenium powder, and deionized water is used as the reaction medium to reduce the influence of impurity ions on the reaction process and product composition.
[0014] In some embodiments of the present invention, both steps (1) and (2) use deionized water as the reaction medium, and no organic solvents or organic ligands are added to the reaction system.
[0015] In some embodiments of the present invention, in step (2), the stirring time is 5-10 min, and the alkali metal hydroxide is sodium hydroxide or potassium hydroxide, more preferably sodium hydroxide.
[0016] In step (2), the molar ratio of copper nitrate trihydrate, silver nitrate, and selenium powder matches the stoichiometric ratio of CuAgSe. Sodium hydroxide is used to provide a strongly alkaline reaction environment, regulate the state of precursor species, and control subsequent reactions, nucleation, and grain growth processes. By controlling the concentration of sodium hydroxide and the stirring time, the uniformity of the reaction system can be improved, allowing the copper source, silver source, and selenium-containing precursor to be fully mixed, and forming micron-sized CuAgSe particles under subsequent hydrothermal conditions.
[0017] In some embodiments of the present invention, the hydrothermal reaction temperature in step (3) is 180 °C.
[0018] In step (3), the hydrothermal reaction temperature is 160-200 °C, and the time is 12-24 h. This temperature and time range provides suitable conditions for precursor reaction, ion migration, and grain growth, which is beneficial for improving the crystal integrity and phase purity of the product. Too low a hydrothermal temperature or too short a reaction time may lead to incomplete reaction; too high a hydrothermal temperature or too long a reaction time may cause excessive grain growth and uneven particle size distribution. Therefore, by controlling the hydrothermal reaction temperature and time, the controllable preparation of CuAgSe micron-sized particles can be achieved.
[0019] In some embodiments of the present invention, in step (4), the product is washed sequentially with deionized water and anhydrous ethanol; the centrifugation speed for solid-liquid separation is 6000-9000 rpm, and each centrifugation lasts for 5-10 minutes; the drying method is vacuum drying, the drying temperature is 60-80 ℃, and the drying time is 3-8 h. Washing can remove residual soluble byproducts and unreacted components from the product, while vacuum drying helps to reduce the residual moisture and solvent content in the powder.
[0020] In some embodiments of the present invention, in step (4), the particle size of the near-room temperature CuAgSe micron thermoelectric material is 2-3 μm.
[0021] In another aspect, the present invention provides a method for preparing a CuAgSe thermoelectric bulk material. According to an embodiment of the present invention, the method includes the following steps:
[0022] The near-room temperature CuAgSe micron thermoelectric material prepared by the hydrothermal method was annealed in a nitrogen atmosphere. The annealed powder was then ground and hot-pressed and sintered to obtain CuAgSe thermoelectric bulk material.
[0023] In addition, the method for preparing a CuAgSe thermoelectric bulk body according to the above embodiments of the present invention may also have the following additional technical features:
[0024] In some embodiments of the present invention, the annealing temperature is 400 °C, the time for raising the temperature from room temperature to 400 °C is 0.5-1 h, and the holding time is 1-2 h. Annealing is beneficial to promoting the improvement of the powder crystal structure and the homogenization of the composition, reducing the influence of adsorbates on the powder surface and some residual components on the subsequent sintering process, thereby improving the thermal stability and sintering adaptability of the powder.
[0025] The hot-pressing sintering temperature is 350-400 ℃, the pressure is 48-50 MPa, and the holding time is 8-10 min. Under these hot-pressing conditions, the synergistic effect of temperature and pressure promotes particle rearrangement, interparticle diffusion, and interfacial bonding, thereby achieving densification of the CuAgSe powder. The sintering temperature can promote powder densification while reducing the risk of component segregation, abnormal grain growth, and thermal stress accumulation that may be caused by excessively high temperatures. The sintering pressure and holding time are beneficial for obtaining CuAgSe thermoelectric bulk materials with complete structure, uniform microstructure, and high relative density, while improving the stability and repeatability of the hot-pressing process.
[0026] In some embodiments of the present invention, the relative density of the CuAgSe thermoelectric bulk is 92%-95%.
[0027] Compared with the prior art, the beneficial effects of the present invention are:
[0028] (1) Controllable preparation of CuAgSe micron particles: This invention introduces 1.5-2.0 mol / L of alkali metal hydroxide into an aqueous selenium-containing precursor system and combines it with a hydrothermal reaction at 160-200 °C. The nucleation and growth of CuAgSe are regulated by the synergistic effect of the strongly alkaline environment and the hydrothermal crystallization process, resulting in CuAgSe micron powder with a main particle size of 2-3 μm and relatively pure phase. This method uses water as the reaction medium and does not use organic ligands such as oleylamine or dodecyl mercaptan, or high-boiling-point organic solvents, which can reduce the problems of organic residues and severe agglomeration of nanoparticles. At the same time, a highly active selenium-containing precursor system is constructed by reducing selenium powder with sodium borohydride, and the controllable growth of CuAgSe from the nanoscale to the microscale is achieved by combining it with a hydrothermal reaction, providing a new technical path for obtaining high-quality CuAgSe micron thermoelectric powder.
[0029] (2) Improve the sintering adaptability and bulk structure stability of the powder: After annealing and hot pressing sintering, the prepared CuAgSe micron thermoelectric powder can obtain a dense bulk with a relative density of 92%-95%. Compared with nanocrystalline powder prepared by colloidal method, the micron-sized particles have a lower degree of agglomeration, which is more conducive to particle rearrangement, interfacial bonding and bulk densification. This can reduce the risk of bulk deformation, cracking or hot pressing mold failure caused by nanoparticle agglomeration, phase transformation volume change and thermal stress accumulation, and improve the stability of CuAgSe bulk preparation process.
[0030] (3) It possesses both good near-room temperature thermoelectric properties and process feasibility: Under conditions without elemental doping, second-phase recombination, or other complex performance regulation, the obtained CuAgSe bulk exhibits good thermoelectric transport properties in the range of 300-450 K, and the thermoelectric figure of merit zT can reach about 0.8 at 450 K, indicating that the CuAgSe microstructure constructed in this invention can itself obtain good near-room temperature thermoelectric properties. At the same time, the raw materials are readily available, the process flow is simple, and the reaction parameters are clear. In the examples, the powder yield can reach about 94%, and the target phase can be stably obtained under different hydrothermal temperatures and reaction times, which has good process stability and a basis for further batch preparation and application. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the CuAgSe thermoelectric bulk molding process in Application Example 1 of the present invention;
[0032] Figure 2 The X-ray diffraction (XRD) patterns of CuAgSe powders prepared in Examples 1-3 and Comparative Example 1 of this invention are shown below.
[0033] Figure 3The images are scanning electron microscope (SEM) images of CuAgSe powder prepared in Example 1 and Comparative Example 1 before annealing, where a) is Example 1 and b) is Comparative Example 1, and both have a magnification of 10 K times.
[0034] Figure 4 The images shown are scanning electron microscope (SEM) images of the cross-section of CuAgSe bulk obtained in Application Example 1 and Comparative Example 2 of the present invention, where a) is Application Example 1 and b) is Comparative Example 2, and both have a magnification of 10 K times.
[0035] Figure 5 The curves showing the change in electrical transport properties of CuAgSe bulk materials prepared in Application Example 1 and Comparative Example 2 of this invention as a function of temperature are shown in Figure a), where σ is the electrical conductivity and S is the Seebeck coefficient.
[0036] Figure 6 The curves showing the thermal transport properties of CuAgSe bulk materials prepared in Application Example 1 and Comparative Example 2 of this invention as a function of temperature are shown, where a) is the total thermal conductivity κ and b) is the lattice thermal conductivity κ. L ;
[0037] Figure 7 The curves showing the overall thermoelectric performance of CuAgSe bulk materials prepared in Application Example 1 and Comparative Example 2 of this invention as a function of temperature are shown, where a) is the power factor PF and b) is the dimensionless thermoelectric figure of merit zT. Detailed Implementation
[0038] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments and accompanying drawings. It should be understood that the embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Various equivalent substitutions or modifications made by those skilled in the art to the embodiments without departing from the technical concept of the present invention should fall within the scope of protection of the present invention.
[0039] Example 1
[0040] A hydrothermal preparation method for CuAgSe micromaterials includes the following steps:
[0041] (1) Preparation of reaction precursor solution
[0042] a. Add 100 mL of deionized water to a 250 mL three-necked flask. Under nitrogen protection, add 30 mmol of sodium borohydride (NaBH4) and 10 mmol of selenium powder (Se) sequentially. Stir continuously for about 30 min until the selenium powder has fully reacted and a homogeneous solution with no obvious solid residue is formed, yielding a solution containing reduced HSe. - Anionic precursor solution.
[0043] b. Add 8 g of sodium hydroxide (NaOH) to the above anionic precursor solution and continue stirring until the sodium hydroxide is completely dissolved. Then add 10 mmol of copper nitrate trihydrate [Cu(NO3)2·3H2O] and 10 mmol of silver nitrate (AgNO3), and continue stirring for 10 min to ensure thorough mixing of the reactants, thus obtaining the reaction precursor solution. The concentration of sodium hydroxide is 2.0 mol / L based on the initial volume of deionized water.
[0044] (2) Preparation of CuAgSe micron thermoelectric material
[0045] c. Transfer the entire reaction precursor solution obtained in step (1) into a stainless steel high-pressure reactor with a polytetrafluoroethylene liner, seal it, place it in an oven, heat it to 180 °C, and keep it at that temperature for 24 h. After the reaction is complete, allow the reactor to cool naturally to room temperature.
[0046] d. The obtained reaction products were centrifuged and washed sequentially with deionized water and anhydrous ethanol. The products were washed twice with deionized water and twice with anhydrous ethanol; each centrifugation was performed at 6000 r / min for 5 min.
[0047] e. The washed solid product was placed in a vacuum drying oven and dried at 60 °C for 8 h to obtain CuAgSe micron-sized thermoelectric material. The mass of the obtained CuAgSe micron-sized thermoelectric material was approximately 2.35 g, and the yield was approximately 94% based on the theoretical CuAgSe yield corresponding to 10 mmol of selenium powder.
[0048] Example 2
[0049] A hydrothermal preparation method for CuAgSe micromaterials differs from Example 1 only in that: in step (2)c, the hydrothermal reaction temperature is 180 °C and the reaction time is 12 h, while the other parameters and steps are the same as in Example 1.
[0050] Example 3
[0051] A hydrothermal preparation method for CuAgSe micromaterials differs from Example 1 only in that: in step (2)c, the hydrothermal reaction temperature is 160 °C and the reaction time is 24 h, while the other parameters and steps are the same as in Example 1.
[0052] Comparative Example 1
[0053] The preparation of CuAgSe nanocrystalline powder using a colloidal method includes the following steps:
[0054] (1) Preparation of the reaction system of selenium precursor and metal salt
[0055] a. Add 10 mmol of selenium powder, 10 mL of oleylamine, and 10 mL of 1-dodecyl mercaptan to a 50 mL three-necked flask and perform a vacuum-nitrogen purging cycle to remove oxygen from the reaction system. Then, under nitrogen protection, continue stirring until the selenium powder is completely dissolved, yielding a brown selenium precursor solution. The volume of the obtained selenium precursor solution is approximately 20 mL, and the concentration is approximately 0.5 mol / L.
[0056] b. Add 10 mmol of cuprous chloride (CuCl) and 10 mmol of silver nitrate (AgNO3) to a 250 mL three-necked flask, then add 120 mL of oleylamine, and stir magnetically at room temperature to obtain the metal salt reaction system.
[0057] (2) Preparation of CuAgSe nanocrystals
[0058] c. The metal salt reaction system obtained in step (1)b was stirred at room temperature and subjected to a vacuum-nitrogen cycle three times, with stirring continuing for 10 min after each nitrogen purging. The reaction system was then heated to 80 °C and subjected to vacuum treatment at this temperature for 60 min; then heated to 130 °C under vacuum and held for 10 min to remove moisture and low-boiling-point components. After the above treatment, the reaction system was heated to 270 °C under nitrogen protection to form a cation reaction mother liquor. 20 mL of the 0.5 mol / L selenium precursor solution prepared in step (1)a was rapidly injected into the cation reaction mother liquor using a syringe, and the reaction was carried out at 270 °C for 30 min. After the reaction was completed, the reaction system was cooled to approximately 70 °C using a water bath, and then 30 mL of oleic acid (OA) was added for ligand exchange treatment.
[0059] d. The cooled reaction product was washed three times by centrifugation with n-hexane and anhydrous ethanol; each centrifugation was performed at 8000 r / min for 5 min. The washed solid product was then placed in a vacuum drying oven and dried at 60 °C for 6 h to obtain CuAgSe nanocrystalline powder.
[0060] The powders obtained in Examples 1-3 and Comparative Example 1 were tested using X-ray diffraction (XRD). Figure 2 As shown, the main diffraction peaks of each sample matched the characteristic peaks of the CuAgSe standard diffraction cards PDF#010-0451 and PDF#025-1180, and no obvious impurity phase diffraction peaks were observed within the instrument's detection range. These results indicate that products with CuAgSe as the main phase can be obtained under hydrothermal reaction conditions of 160-180℃ and 12-24h, demonstrating that the preparation method described in this invention exhibits good phase formation stability within a certain reaction temperature and time range.
[0061] The CuAgSe powders of Example 1 and Comparative Example 1 were characterized using a field emission scanning electron microscope (Hitachi Regulus 8230). Figure 3 As shown, the powder obtained in Example 1 mainly consists of micron-sized particles, with particle sizes primarily distributed between 2 and 3 μm. In contrast, the product prepared by the colloidal method in Comparative Example 1 mainly consists of fine nanoparticles with significant particle agglomeration. These results demonstrate that the present invention, through the synergistic regulation of a strongly alkaline aqueous precursor system and the hydrothermal crystallization process, achieves the growth of CuAgSe particles from the nanoscale to the microscale, providing a particle structure basis different from colloidal nanocrystals for subsequent powder sintering.
[0062] Application Example 1
[0063] The method for preparing CuAgSe thermoelectric bulk material includes the following steps: The CuAgSe powder obtained in Example 1 is annealed under a nitrogen atmosphere, with the temperature raised from room temperature to 400 °C for 40 min, and held at 400 °C for 2 h. The annealed powder is then ground in a glove box and placed into a graphite mold with an inner diameter of 10 mm and lined with 0.20 mm thick carbon paper. Hot pressing sintering is then performed under nitrogen protection. The hot pressing temperature is 400 °C, the pressure is 50 MPa, and the holding time is 10 min. The resulting disc-shaped bulk material has a diameter of approximately 10 mm, a thickness of approximately 1.5 mm, and a relative density of 92%-95%.
[0064] like Figure 1 As shown, the preparation process of CuAgSe thermoelectric material bulk material mainly includes the preparation of a selenium-containing precursor solution, hydrothermal reaction, annealing, and hot-pressing sintering. First, a precursor solution containing reduced selenium species (NaHSe) is obtained under nitrogen protection; then sodium hydroxide, copper nitrate trihydrate, and silver nitrate are added, and after thorough mixing, the mixture is transferred to a high-pressure reactor for hydrothermal reaction. The resulting CuAgSe micron-sized powder is annealed under nitrogen atmosphere and then hot-pressed to obtain the CuAgSe thermoelectric bulk material.
[0065] Comparative Example 2
[0066] The method for preparing CuAgSe thermoelectric bulk material differs from Application Example 1 only in that: instead of using the CuAgSe micron thermoelectric material prepared in Example 1, CuAgSe nanocrystalline powder prepared in Comparative Example 1 is used. All other parameters and steps are the same as in Application Example 1.
[0067] like Figure 4As shown, there are significant differences in the microstructure of the CuAgSe thermoelectric material bulk cross-sections of Application Example 1 and Comparative Example 2. The bulk cross-section of Application Example 1 is generally dense, with more continuous bonding between grains and fewer obvious pores; the bulk of Comparative Example 2 still retains a finer particle structure, and more interparticle pores can be observed. The above results indicate that the CuAgSe micron powder prepared by this invention has good adaptability to hot pressing sintering, which is beneficial to particle rearrangement, interfacial bonding, and the formation of dense bulk materials.
[0068] The conductivity (σ) and Seebeck coefficient (S) of the blocks obtained from Test Case 1 and Comparative Example 2 were tested using the Seebeck coefficient / resistance testing system (LSR-3) in the range of 300-450 K. Figure 5 As shown in Figure a, the sample in Application Example 1 exhibits higher σ values than Comparative Example 2 throughout the entire test temperature range, and the decrease in σ with increasing temperature is relatively small, demonstrating more stable electrical transport characteristics. Figure 5 As shown in b, the S values of both samples are negative, indicating that they exhibit N-type conductivity within the test temperature range. The absolute value of S in Application Example 1 is significantly higher than that in Comparative Example 2, and remains stable or slightly increases with increasing temperature, while the absolute value of S in Comparative Example 2 decreases significantly with increasing temperature. This result indicates that the CuAgSe bulk material obtained in this invention can maintain a large negative S while maintaining a high σ, which is beneficial for improving its near-room temperature power factor (PF).
[0069] The thermal diffusivity (α) of the bulk samples was determined using an LFA 1000 laser scintillation analyzer manufactured by LINSEIS GmbH, Germany. Sample density (ρ) was determined using the Archimedes displacement method, and relative density was calculated as the ratio of the measured density to the theoretical density of CuAgSe; specific heat capacity (C...) was also measured. p Calculated according to the Dulong-Petty law. Combining α, ρ, and C p The total thermal conductivity (κ) and lattice thermal conductivity (κ) were calculated. L Then, the total thermal conductivity is subtracted from the electronic thermal conductivity (κ). e (Obtained) For example Figure 6 As shown in Figure a, the κ value of the block in Application Example 1 is higher than that in Comparative Example 2 at lower temperatures. As the temperature increases, the κ values of both gradually decrease and tend to converge. Figure 6 As shown in b, the κ of Example 1 is applied. L The value of κ decreased continuously with increasing temperature, and was significantly lower than that of Comparative Example 2 in the higher temperature range; in contrast, the value of κ in Comparative Example 2 was significantly lower. L The κ value initially increases with increasing temperature, then the change becomes smaller. These results indicate that the CuAgSe microstructure prepared in this invention maintains good electrical transport properties while reducing κ over a higher temperature range. L This is conducive to achieving synergistic optimization of electrical and thermal transport performance.
[0070] like Figure 7 As shown in Figure a, the power factor (PF) of the bulk material in Application Example 1 is maintained at approximately 2.0 mW·m in the range of 300–450 K. -1 ·K -2 The PF of Comparative Example 2 decreases continuously with increasing temperature, and approaches zero near 450 K. Figure 7 As shown in b, the dimensionless thermoelectric figure of merit zT of Application Example 1 increases continuously with increasing temperature, reaching approximately 0.8 at 450 K; while the zT of Comparative Example 2 gradually decreases with increasing temperature. These results demonstrate that, without elemental doping or second-phase recombination, the CuAgSe bulk prepared by this invention exhibits relatively stable power factor (PF) and high overall thermoelectric performance in the near-room temperature range.
[0071] In summary, this invention achieves the preparation of relatively pure CuAgSe micron-sized powders by introducing a hydrothermal crystallization process into a strongly alkaline aqueous selenium-containing precursor system. Compared with CuAgSe nanocrystals prepared by colloidal methods, the powder obtained by this invention has larger particle size and lower agglomeration. After the same annealing and hot-pressing treatments, it can form a dense bulk with a relative density of 92%-95%, and exhibits a high and stable power factor in the range of 300-450 K, with zT reaching approximately 0.8 at 450 K. Therefore, the method described in this invention combines the advantages of micron-sized structure control, sintering adaptability, and near-room temperature thermoelectric performance, providing a reliable preparation route for near-room temperature thermoelectric conversion applications of CuAgSe materials.
[0072] The above content is merely an example and illustration of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort should fall within the scope of protection of the present invention.
Claims
1. A hydrothermal preparation method for CuAgSe micron-sized materials, characterized in that, Includes the following steps: (1) Under an inert atmosphere, the selenium source was added to an aqueous solution containing sodium borohydride and stirred to react, resulting in a precursor solution containing reduced selenium species. (2) Add alkali metal hydroxide to the precursor solution so that the concentration of the alkali metal hydroxide is 1.5-2.0 mol / L based on the initial aqueous phase volume. Then add copper nitrate trihydrate and silver nitrate in a molar ratio of Cu, Ag and Se of 1:1:1 and stir to obtain a mixed reaction solution. (3) Place the mixed reaction solution in a sealed reaction container and carry out a hydrothermal reaction at 160-200 °C for 12-24 h; (4) After the reaction is completed, the product is cooled, and the product is subjected to solid-liquid separation, washing and drying to obtain near-room temperature CuAgSe micron thermoelectric material.
2. The hydrothermal preparation method of CuAgSe micromaterial according to claim 1, characterized in that: In step (1), the molar ratio of the selenium source to sodium borohydride is 1:(2-3); the stirring reaction time is 0.5-1 h; and the inert atmosphere is nitrogen or argon.
3. The hydrothermal preparation method of CuAgSe micromaterial according to claim 1, characterized in that: Both steps (1) and (2) use deionized water as the reaction medium, and no organic solvents or organic ligands are added to the reaction system.
4. The hydrothermal preparation method of CuAgSe micron-sized material according to claim 1, characterized in that: In step (2), the alkali metal hydroxide is sodium hydroxide or potassium hydroxide, and the stirring time is 5-10 min.
5. The hydrothermal preparation method of CuAgSe micron-sized material according to claim 1, characterized in that: In step (3), the hydrothermal reaction temperature is 180 ℃.
6. The hydrothermal preparation method of CuAgSe micron-sized material according to claim 1, characterized in that: In step (4), the solid-liquid separation is carried out by washing with deionized water and anhydrous ethanol in sequence; the centrifugation speed is 6000-9000 rpm, and each centrifugation is 5-10 min; the drying method is vacuum drying, the drying temperature is 60-80 ℃, and the drying time is 3-8 h.
7. The hydrothermal preparation method of CuAgSe micromaterial according to claim 1, characterized in that: In step (4), the particle size of the near-room temperature CuAgSe micron thermoelectric material is 2-3 μm.
8. A method for preparing a CuAgSe thermoelectric bulk material, characterized in that, Includes the following steps: The CuAgSe micron material prepared by the hydrothermal preparation method according to any one of claims 1-7 is annealed under a nitrogen atmosphere, and the annealed powder is ground and then hot-pressed and sintered to obtain CuAgSe thermoelectric bulk material.
9. The method for preparing a CuAgSe thermoelectric bulk material according to claim 8, characterized in that: The annealing treatment is performed at a temperature of 400 ℃, with the time to rise from room temperature to 400 ℃ being 0.5-1 h and the holding time being 1-2 h; the hot pressing sintering temperature is 350-400 ℃, the pressure is 48-50 MPa, and the holding time is 8-10 min.
10. The method for preparing a CuAgSe thermoelectric bulk material according to claim 8, characterized in that: The relative density of the CuAgSe thermoelectric bulk material is 92%-95%.